ANALYSIS OF TYPES OF CODE SWITCHING AND CODE MIXING IN THE BUMI MANUSIA FILM BY HANUNG BRAMANTYO - Talullah Janna Delian Devanty; R Agus Budiharto (The Ellite of Unira, 2022)
There are many kinds of literary work such as novel, poem, film, etc. Sometimes in the work there is a usage of many languages because of the idea and the creativity of the creators to make their project different from others’. For example, Bumi Manusia film which the characters have different ethnic or racial background so there is many different languages used. This makes code switching and code mixing happened. This study aims to find the use of code switching and code mixing in the film Bumi Manusia, then determine each type based on the selected reference, then determine the reasons for using code switching and code mixing in the film.This research was conducted by watching movies repeatedly, recording dialogues or conversations which are code switching and code mixing, determining the data for each type (whether including code switching or code mixing), after that determining the types and finally analyzing the causes of its use. The results show that the use of code-switching in the film Bumi Manusia is more than the use of code-mixing. And the reason for using code switching and code mixing the most widely used is because of solidarity and to soften or strengthen requests or command.